2017
DOI: 10.1111/cdev.12910
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental Anger and Effortful Control, Teacher–Child Conflict, and Externalizing Behavior Across the Elementary School Years

Abstract: This study examined teacher-child conflict as a possible mediator of the effects of temperamental anger and effortful control on subsequent externalizing behavior. Reciprocal influences between teacher-child conflict and externalizing behavior were also examined. Participants were 1,152 children (49% female; 81.6% non-Hispanic White) from the Study of Early Child Care and Youth Development. Multivariate growth curve modeling revealed that greater effortful control at age 54 months indirectly predicted lower le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Taken together, several general conclusions can be drawn from variable-centered studies on TSR and conduct problems. Although these studies corroborate the premise that there are strong concurrent and prospective associations between TSR and conduct problems (Doumen et al, 2008;Hamre & Pianta, 2001;Ly & Zhou, 2018;Mejia & Hoglund, 2016;Pakarinen et al, 2018;Skalická, Stenseng, & Wichstrøm, 2015;Zhang & Sun, 2011), there are stronger and more consistent associations between conduct problems and conflict than warmth (Ly & Zhou, 2018;Mejia & Hoglund, 2016) and for teacher as compared to parent-reported conduct problems (Crockett et al, 2018;. However, most of these studies have been based on short-term longitudinal designs to investigate discrete developmental periods or stages (e.g., within a school year or across a few grade levels) and have been conducted in early and middle childhood.…”
Section: Children's Conduct Problems and Teacher-student Relationship Qualitysupporting
confidence: 62%
See 1 more Smart Citation
“…Taken together, several general conclusions can be drawn from variable-centered studies on TSR and conduct problems. Although these studies corroborate the premise that there are strong concurrent and prospective associations between TSR and conduct problems (Doumen et al, 2008;Hamre & Pianta, 2001;Ly & Zhou, 2018;Mejia & Hoglund, 2016;Pakarinen et al, 2018;Skalická, Stenseng, & Wichstrøm, 2015;Zhang & Sun, 2011), there are stronger and more consistent associations between conduct problems and conflict than warmth (Ly & Zhou, 2018;Mejia & Hoglund, 2016) and for teacher as compared to parent-reported conduct problems (Crockett et al, 2018;. However, most of these studies have been based on short-term longitudinal designs to investigate discrete developmental periods or stages (e.g., within a school year or across a few grade levels) and have been conducted in early and middle childhood.…”
Section: Children's Conduct Problems and Teacher-student Relationship Qualitysupporting
confidence: 62%
“…More specifically, conflict increased from kindergarten to Grade 4 and then decreased from Grade 4 to Grade 6 (i.e., an inverse u-shaped trajectory). In contrast, closeness decreased from Kindergarten to Grade 6, with the rate of decline becoming more pronounced in later grades (for similar results, see Crockett, Wasserman, Rudasill, Hoffman, & Kalutskaya, 2018;Lee & Bierman, 2018). Examining a relatively longer developmental period and utilizing a sample of children at risk for academic problems, Wu and Hughes (2015) also reported a declining trend for teacher-student warmth from Grades 1 to 9, with rates of decline being more pronounced during the transition to middle school.…”
Section: Development and Continuity Of Teacher-student Relationshipsmentioning
confidence: 77%
“…These findings are generally consistent with research based on Bowlby's (1969) theoretical contentions, suggesting that children with externalizing behavior tend to express their feelings of rejection and insecure attachment in the form of frustration, anger, and distress (Carlson & Sroufe, 1995;Madigan et al, 2016). Moreover, studies using questionnaire measures of student-teacher relationship quality (e.g., Birch & Ladd, 1998;Crockett et al, 2018;Hamre et al, 2008;Henricsson & Rydell, 2004) have shown that teachers' reports of problem behaviors may explain as much as 53% of the variance in conflictual studentteacher relationships. In contrast to those studies, though, we used a multi-informant approach to evaluate linkages between child behavior and student-teacher relationships.…”
Section: Associations Between Social-emotional Child Behaviors and Mental Representationssupporting
confidence: 85%
“…In studies employing child reports Murray & Zvoch, 2011) and teacher reports of relationship quality (e.g., Birch & Ladd, 1998;Henricsson & Rydell, 2004;Jerome et al, 2009;Zhang & Sun, 2011), children with externalizing behavior have more conflict with teachers. Cross-lagged longitudinal studies (Crockett et al, 2018;Doumen et al, 2008;Mejia & Hoglund, 2016;Roorda et al, 2014) even found evidence for small reciprocal associations across elementary grades, with students' externalizing behavior predicting teacher-reported conflict and vice versa.…”
Section: Conflictmentioning
confidence: 99%
“…The proposed framework organises TSI into three domains reflecting distinct features of these interactions; namely, emotional support (for instance, acknowledging children's emotions and experiences, and sensitively responding to them), classroom organisation (for instance, clarifying the rules and expectations), and instructional support (for instance, asking open-ended questions) (Downer et al, 2010;Hamre et al, 2013). In agreement with the framework, numerous observational studies have shown a correlation between the quality of TSI at the classroom level (i.e., emotional, instructional, and organisational support) and children's EF/SR skills (e.g., Cadima et al, 2015b;Crockett et al, 2017;Acar et al, 2018;Goble et al, 2019; for a review, see Cumming et al, 2019). For instance, a recent meta-analysis (Vandenbroucke et al, 2017(Vandenbroucke et al, , 2018 informs further regarding the strength of the correlations between these concepts, and overall effect sizes indicate small to medium associations between TSI and working memory, and a small association with inhibition, but not cognitive flexibility.…”
Section: Introductionmentioning
confidence: 72%